Liquid scintillator composition optimization for use in ultra-high energy cosmic ray detector systems - Beznosko, Dmitriy; Batyrkhanov, Ayan; Iakovlev, Alexander; Yelshibekov, Khalykbek (ISVHECRI 2016, 2016)
The Horizon-T (HT) detector system and the currently under R&D HT-KZ detector system are designed for the detection of Extensive Air Showers (EAS) with energies above _1016 eV (_1017 eV for HT-KZ). The main challenges in both detector systems are the fast time resolutions needed for studying the temporary structure of EAS, and the extremely wide dynamic range needed to study the spatial distribution of charged particles in EAS disks. In order to detect the low-density of charged particles far from the EAS axis, a large-area detector is needed. Liquid scintillator with low cost would be a possible solution for such a detector, including the recently developed safe and low-cost water-based liquid scintillators. Liquid organic scintillators give a fast and high light yield (LY) for charged particle detection. It is similar to plastic scintillator in properties but is cost effective for large volumes. With liquid scintillator, one can create detection volumes that are symmetric and yet retain high LY detection. Different wavelength shifters affect the scintillation light by changing the output spectrum into the best detection region. Results of the latest studies of the components optimization in the liquid scintillator formulae are presented